Contributions of various transmission paths to speech privacy of open ceiling meeting rooms in open-plan offices. (November 2016) - Yu, Jingxia; Wang, Shuping; Qiu, Xiaojun; Shaid, Abu; Wang, Lijing
Abstract: Installing open ceiling meeting rooms inside a large open-plan office provides a solution to increase speech privacy and to reduce speech disturbance in the office. The open ceiling meeting rooms have advantages of low cost construction and flexibility, but have lower speech privacy than that of enclosed rooms due to the open ceiling. Existing research shows that many factors should be taken into account to achieve good speech privacy in open-plan offices and improving only one of these factors may result in little improvement, so it is important to distinguish contributions of different acoustic transmission paths of open ceiling meeting rooms in open-plan offices. This paper proposes an impulse response separation method to quantify contributions of various acoustic paths of open ceiling rooms on speech privacy in open-plan offices. The method is verified with simulations based on the Odeon software and the experiments carried out in 3 different types of rooms. Finally, the proposed method is applied to the Fabpod, a semi enclosed meeting room located in a large indoor office at the Design Research Institute of the RMIT University, to obtain the contributions of different acoustic transmission paths to its speech privacy. The method proposed in this paper and the knowledge obtained are useful for architects to improve the acoustic performance of the next generation Fabpods which are now under design at RMIT University.